Multiplex Hybrid Capture Improves the Deep Detection of Antimicrobial Resistance Genes from Wastewater Treatment Plant Effluents to Assess Environmental Issues - Sekizuka, Tsuyoshi; Yamaguchi, Nobuyasu; Kanamori, Hajime; Kuroda, Makoto (Microbial drug resistance (Larchmont, N.Y.), 2023)
Metagenomic sequencing (mDNA-seq) is one of the best approaches to address antimicrobial resistance (AMR) issues and characterize AMR genes (ARGs) and their host bacteria (ARB); however, the sensitivity provided is insufficient for the overall detection in wastewater treatment plant (WWTP) effluents because the effluent is well treated. This study investigated the multiplex hybrid capture (xHYB) method (QIAseq × HYB AMR Panel) and its potential to increase AMR assessment sensitivity. The mDNA-Seq analysis suggested that the WWTP effluents had an average of 104 reads per kilobase of gene per million (RPKM) for the detection of all targeted ARGs, whereas xHYB significantly improved detection at 601,576 RPKM, indicating an average 5,805-fold increase in sensitivity. For instance, was detected at 15 and 114,229 RPKM using mDNA-seq and xHYB, respectively. The , , and gene variants were not detected by mDNA-Seq but were detected by xHYB at 67, 20, and 1,010 RPKM, respectively. This study demonstrates that the multiplex xHYB method could be a suitable evaluation standard with high sensitivity and specificity for deep-dive detection, highlighting a broader illustration of ongoing dissemination in the entire community.